Analisis Keandalan Dan Penjadwalan Pemeliharaan Mesin Line Corrugated Dan Flexo Serta Optimasi Persediaan Sparepart Di Perusahahan Pembuatan Karton Box - Nurdianto, Donny; Widiasih, Wiwin (Universitas Muhammadiyah Surabaya Publishing, 2025)
The corrugated box packaging industry plays an essential role in supporting the supply chain of various manufacturing sectors, making machine reliability a critical factor in ensuring production continuity. This study was conducted at a corrugated box manufacturing company in Gresik that operates corrugated line and flexo machines under a three-shift system with high production capacity. Based on downtime data from January 2024 to June 2025, it was found that the failure frequency of machine components was relatively high and had a significant impact on the production flow, particularly because the company still relies on corrective maintenance and does not yet have a structured spare parts control system.The research adopts a quantitative approach, involving calculations of Mean Time To Failure (MTTF), Mean Time To Repair (MTTR), Mean Time Between Failures (MTBF), reliability analysis using Weibull, Normal, and Exponential distributions, as well as determining the Reorder Point (ROP) based on actual demand and procurement lead time. The results show that most machine components exhibit low reliability levels, ranging from 37% to 66%, with failure patterns predominantly occurring in the wear-out phase. Based on these findings, a reliability-based preventive maintenance schedule was developed, allowing maintenance actions to be performed proactively rather than reactively.In addition, the ROP calculation indicates that the required spare parts range from 1 to 9 units depending on the component’s risk level and failure frequency. Overall, the implementation of preventive maintenance and ROP proves effective in improving maintenance performance, reducing downtime, and supporting the smooth operation of corrugated box production.